Dedication to Community Engagement: A Higher Education Conundrum? - Nicole Nicotera; Nick Cutforth; Eric Fretz; Sheila Summers Thompson (The University of Alabama, 2022)
Universities and colleges are increasingly providing internal grants to encourage faculty and staff involvement in community-based research and service-learning projects; however, little attention has been given to the impact of institutional support of these efforts. This qualitative study employed focus group interviews with 17 faculty and staff at one mid-size private research university (high activity) to explore the impact of institutional funding on their professional roles and practice of community-engaged work. Findings revealed that community-based projects energized the participants, helped them make their academic work relevant in communities, created formal and informal university-community partnerships, and elevated the University's public image. However, a conundrum was evident in the tension between the University's public expression of the importance of community engagement and participants' concerns that the traditional academic reward structure could jeopardize their long-term commitment to community work. A framework is offered that may assist institutions that are pondering or have already committed to using institutional dollars to support engaged scholarship.